Annual Reports of the Various Departments of the City of Columbus, Together with a Financial Statement of the Receipts and Disbursements for the Year Ending December 31, 1893, at 16-20, Ordinance No. 8191-Making Certain Offenses Therein Named Misdemeanors, § 9-Concealed Weapons & § 25-Firearms, Firecrackers, Etc. Passed January 22, 1894. - (:unkn) unknown (My University, 1894)
Whoever shall wear under his clothes, or concealed about his person, any pistol or revolver, colt, billy, slungshot, brass knuckles or knuckles of lead, dirk, dagger or any knife resembing a bowie knife or any other dangerous or deadly weapon within the corporate limits of the city of Columbus, shall, on conviction thereof, be fined not exceeding one hundred dollars for each and every offense, SEC. 25. Whoever shall throw, cast or let off any skyrocket, squib, cracker, firework or other thing charged with gunpowder; or discharge any common gun or pistol in this city, without a written permit from the mayor, shall be deemed guilty of a misdemeanor
Keywords: CARRY - CONCEALED; DISCHARGE